An object-oriented pramework (OOF) for document management system (DMS) / Siti Munirah Che Mat - Che Mat, Siti Munirah (2011)
These thesis contain research on the process in developing of Document Management System using Object - oriented Frameworks. This paper provides the requirement on research project and also the system development life cycle as methodology and approach to achieve this Document Management System for the Hansard document. Hansard is meeting proceeding document among members of parliament of representative and senate which certain country called text of parliament debate. Document Management System is a computer system or programs used to track and store electronic documents .The goal of document management is to share , accessible, retrievable , and managed by a standard features of system. Object-oriented Frameworks was applied to reuse the designs of all or a part of a software system in Document Management System which focusing on query extension on searching in order to solve the current problem in searching of hansard that does not provide any query suggestion in assisting user to get intended result. Object-oriented will capture the functionality common to several similar applications and domain which save time for the design phase and give good guideline in developing a system for a new programmer. In future this design of DMS system can be modified and reuse for another aspect or attribute that related to the Hansard document and also others object within the same domain of system.